1986
DOI: 10.1007/bf01711651
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarontherapie — Verhalten von Serum- und Fettgewebskonzentrationen

Abstract: Thirty-eight patients with refractory supraventricular and ventricular tachyarrhythmias were administered a mean oral dosage of 400 mg amiodarone daily (200-600 mg). A high-pressure liquid chromatography method was used to measure serum concentrations of amiodarone and its metabolite desethylamiodarone after one week, one month, three months, and then at 6-month intervals. In 24 patients subcutaneous fatty tissue concentrations were also measured. The mean follow-up was 9 months (4 days to 29 months). A linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We had hypothesized that an excessive accumulation of amiodarone would occur in adipose tissue with increased treatment duration, as suggested by some studies [14,16,17] and modelled by some authors [10].The increasing tissue concentrations would have provided a good explanation for the rising incidence of amiodaronerelated toxicity over time.This could have provided a rationale for the reduction of maintenance doses, which has …”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…We had hypothesized that an excessive accumulation of amiodarone would occur in adipose tissue with increased treatment duration, as suggested by some studies [14,16,17] and modelled by some authors [10].The increasing tissue concentrations would have provided a good explanation for the rising incidence of amiodaronerelated toxicity over time.This could have provided a rationale for the reduction of maintenance doses, which has …”
Section: Discussionmentioning
confidence: 90%
“…Other studies have yielded conflicting results. Two studies [17,21] found significantly higher serum levels of amiodarone and its metabolite in patients with adverse effects. One of these two studies, by Gonska et al [17], also found higher concentrations in subcutaneous adipose tissue in patients with adverse effects.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations